2007
DOI: 10.1074/jbc.m703446200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Subunit Structure of Clostridium botulinum Serotype D Toxin Complex with Three Extended Arms

Abstract: The botulinum neurotoxins (BoNTs) are the most potent toxins known in nature, causing the lethal disease known as botulism in humans and animals. The BoNTs act by inhibiting neurotransmitter release from cholinergic synapses. Clostridium botulinum strains produce large BoNTs toxin complexes, which include auxiliary non-toxic proteins that appear not only to protect BoNTs from the hostile environment of the digestive tract but also to assist BoNT translocation across the intestinal mucosal layer. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 33 publications
4
108
0
3
Order By: Relevance
“…The β-trefoil domains of HA-33 from BoNT/A, C, and D are highly similar. However, the domains are capable of twisting against each other by as much as 10°, via the helical linker, suggesting significant inter-domain conformational plasticity (Arndt et al 2005;Hasegawa et al 2007;Inoue et al 2003). HA-17 seems to tightly associate with HA-33, forming a complex that remains bound even in the presence of high concentrations of guanidine hydrochloride .…”
Section: The Structure Of the Ha Proteinsmentioning
confidence: 99%
“…The β-trefoil domains of HA-33 from BoNT/A, C, and D are highly similar. However, the domains are capable of twisting against each other by as much as 10°, via the helical linker, suggesting significant inter-domain conformational plasticity (Arndt et al 2005;Hasegawa et al 2007;Inoue et al 2003). HA-17 seems to tightly associate with HA-33, forming a complex that remains bound even in the presence of high concentrations of guanidine hydrochloride .…”
Section: The Structure Of the Ha Proteinsmentioning
confidence: 99%
“…The concentrations of the toxin complexes in molarity were calculated from the molecular masses of 16S toxin (745 kDa) and 12S toxin (287 kDa) for the type A HApositive and HA-negative toxin complexes; the molecular masses of 16S toxin (744 kDa) and 12S toxin (289 kDa) for the type B HApositive and HA-negative toxin complexes; and the molecular masses of 16S toxin (749 kDa) and 12S toxin (287 kDa) for the type C HApositive and HA-negative toxin complexes, respectively. The molecular mass of each toxin was calculated based on the stoichiometry of subunits contained in the type D toxin complexes (Hasegawa et al, 2007). In the case of the type A HA-positive toxin complex (a mixture of 16S and 19S toxins), one molecule of 19S toxin was regarded as two molecules of 16S toxins, and concentrations of the toxin complex in molarity were calculated as those of 16S toxins.…”
Section: Toxinsmentioning
confidence: 99%
“…In addition, in a human intestinal epithelial cell line (HT-29), the cell surface sialic acid-containing Olinked glycoproteins that are recognized by the type C 16S toxin have been shown to induce the internalization of the toxin into the cells (Nishikawa et al, 2004;Uotsu et al, 2006). Recently, it has been reported that type D HA proteins in the toxin complex enhance permeation through a monolayer of human intestinal epithelial cells (Caco-2) (Niwa et al, 2007). More recently, we have reported that type B HA proteins in the toxin complex have a novel activity, that of disrupting the paracellular barrier of the intestinal epithelium, which facilitates the transepithelial delivery of macromolecules including BoNT (Matsumura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these observations, there is limited information regarding the architecture of the BoNT 16S and 19S PCs. A 2D electron crystallography study of the BoNT/A1 19S PC suggested features with trigonal symmetry (22), and individual electron microscopy (EM) micrographs of the BoNT/D 16S PC suggested that the complex has three extended "arms" (23). Here, we have generated 3D reconstructions of the BoNT/A1, /B, and /E PCs, building on a series of 2D class averages obtained by single particle EM and using the random conical tilt (RCT) approach (24).…”
mentioning
confidence: 99%